2013
DOI: 10.1021/jf304853j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flavone Glucuronide Isomers by Metal Complexation and Tandem Mass Spectrometry: Regioselectivity of Uridine 5′-Diphosphate–Glucuronosyltransferase Isozymes in the Biotransformation of Flavones

Abstract: Flavone Glucuronide isomers of five flavones (chrysin, apigenin, luteolin, baicalein, and scutellarein) were differentiated by collision induced dissociation (CID) of [Co(II) (flavone-H) (4,7-diphenyl-1,10-phenanthroline)2]+ complexes. The complexes were generated via post-column addition of a metal/ligand solution after separation of the glucuronide products generated upon incubation of each flavone with an array of UDP-glucuronosyl-transferase (UGT) isozymes. Elucidation of the glucuronide isomers allowed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
(113 reference statements)
2
20
0
Order By: Relevance
“…As previous studies of other flavonoids have shown, 2729,37 the position of glucuronidation has a strong influence on the CID fragmentation patterns observed. For example, in Figure 3A, a single product, a 7-O-glucuronide, is observed for the reaction of 7-hydroxyflavanone with UGT1A1.…”
Section: Resultssupporting
confidence: 52%
“…As previous studies of other flavonoids have shown, 2729,37 the position of glucuronidation has a strong influence on the CID fragmentation patterns observed. For example, in Figure 3A, a single product, a 7-O-glucuronide, is observed for the reaction of 7-hydroxyflavanone with UGT1A1.…”
Section: Resultssupporting
confidence: 52%
“…Nine components (i.e., peak 1, 2, 4-9, and 12) were identified as gallocatechin, geniposide, luteolin-7-glucoside, Peak 5, 10 and 11 had the same molecular ion [M-H]at m/z 461 and same fragment ions at m/z 284.9, but the different retention time at 19.886 min, 24.362 min, and 27.025 min, respectively. According to the previous results (Borráslinares et al, 2014;Robotham & Brodbelt, 2013;Wang, Lin, Harnly, Harrington, & Chen, 2014), the peak 5 had been identified as luteolin-7-O-β-D-glucuronide and the peak 10 and 11 could be identified as luteolin-5-O-glucuronide, and luteolin-3ʹ-O-glucuronide, respectively.…”
Section: Qualitative Characterization Of Reementioning
confidence: 79%
“…Considering the foreseeable challenges in glycosylation of the phenolic aglycone, we decided to introduce a monosaccharide unit [56] Botting et al, 2008; [57] Yang & Dai et al, 2016; [58] etc. [71] Brodbelt et al, 2013; [72] Wang & Sun et al, 2015 [73]…”
Section: Synthesis Of Cassiasides C and C2 (75 And 74)mentioning
confidence: 99%